School, family, and peer connectedness as protective factors for depression and suicide risk in Spanish adolescents - Pastor, Yolanda; Pérez-Torres, Vanesa; Angulo-Brunet, Ariadna; Nebot-Garcia, Juan E.; Gallardo-Nieto, Elena (Frontiers in Psychology, 2025)
IntroductionSchool, family, and peer connectedness have been shown to be a protective factor for depression and suicide risk in adolescence. However, no comprehensive models have been formulated to assess the influence of each of these factors together on adolescent depression and suicide. The purpose of this study is to analyze the direct and indirect effect—mediated by depressive symptomatology—that different dimensions of social connectedness (family, school, and peers) have on suicide risk.MethodsA battery of tests on depression, suicide risk, and connectedness was administered to a representative sample of 806 Spanish adolescents aged 14 to 17 (M = 16.4, SD = 0.74), by means of an online survey through representative panels.ResultsStructural equation models showed that family connectedness reduces the risk of suicide in adolescence, through both its direct and indirect effects, by virtue of the reduction of depressive symptomatology. The other dimensions of connectedness (peer and school), although negatively related to depression and suicide, were not significant predictors in the models.DiscussionThe practical implications of these results argue for the promotion of family connectedness to prevent adolescent suicide and depression. The lack of prediction regarding peer and school connectedness suggests the influence of possible cultural or contextual factors in Spain, making additional research necessary in this regard.